Solution Properties, Surface Activities And Antimicrobial Effectiveness Of New Biological Surfactants - R. Makhkamov; F. Saidkulov; M. Nurmanova; I. Makhkamova; Sh. Samandarov (Genius Journals, 2024)
The solution properties, surface activities and antimicrobial effectiveness of new biological surface active-substances obtained from microbial cultural liquids and medical plant cells have been investigated. A very good correlation between the foam forming ability and the surface activity of new biological surfactants has been determined. It has been shown, that the stability of surfactant foams significantly determined by the interaction of surfactant molecules in the monolayer. The contact angles of biosurfactant water solutions on hydrophilic and lipophilic surfaces have been investigated. The obtained results with biosurfactant water solutions on the hydrophilic surfaces showed, that lipophilization of hydrophilic surfaces occurred at low biosurfactant concentrations. At higher biosurfactant concentrations the contact angles decreased due to the orientation of biosurfactant molecules by the polar groups on the surfaces. It has been established, that the increase in the cosine of the contact angles at higher surfactant concentrations was associated with the hydrophilization of the surfaces due to the formation of micelles on the surfaces. It has been established that the effect of the biosurfactant structure on the adsorptive modification of surfaces occurs only at low biosurfactant concentrations. The antimicrobial activityes of new biological surfactants water solutions have been investigated. The obtained results showed, that the new biological surfactants water solutions were effective against studied microorganisms. Field tests of new composite preparations based on antimicrobial biological surfactants for plant seeds growth on saline soils were carried out. For field tests, aqueous solutions of composite preparations with new biological surfactants were used. The obtained results showed, that the use of new composite preparations with biological surfactants ensured a good germination and growth of seeds.
Keywords: biosurfactants; wettability; contact angles